Diseño de un modelo de negocio de alojamiento turístico en la Isla de San Andrés que integre experiencias culturales y gastronómicas ancestrales con prácticas de sostenibilidad (2025)
The "Ancestral Cultural and Gastronomic Tourism Accommodation on the Island of San Andrés – Ethnic Roots" project seeks to develop an accommodation proposal that combines the island's cultural and gastronomic richness with a sustainable and authentic approach, with the goal of improving the tourism offering and generating direct benefits for the local community. The main problem addressed is the lack of tourism alternatives that effectively integrate ancestral traditions and local gastronomy, while promoting economic development and heritage conservation. The methodology used includes an analysis of the local context, identification of tourism market needs, strategic project planning, and a financial feasibility study. The expected results are the creation of a tourist space that fosters interaction between visitors and the local culture, as well as job creation and the strengthening of cultural identity. It is concluded that the implementation of this project will significantly contribute to the development of tourism in San Andrés, promoting a sustainable and beneficial model for both tourists and island residents.